Catalisadores sólidos funcionalizados com núcleo magnético de magnetita: síntese, caracterização e aplicação na produção de biodiesel - Santos, Nadiene Aparecida do Vale (2016)
The aim of this work was to develop magnetic sulfated solid catalysts and non sulfated based on La2O3 and Fe3O4 supported on SiO2-Al2O3 (Siral) for the use in biodiesel production via esterification. The produced catalysts were characterized by X Ray Difraction (DRX), Infrared Spectroscopy (FTIR), X Ray Fluorescency (FRX) and Thermogravimetric Analysis (ATG/DTA). The results of DRX revelead the presence of both phases of rare earth and iron oxide with magnetic susceptibility as well as the presence of characteristc phases of aluminosilicates. The catalytic activity was measured in batch reactor using as reaction model methyl esterification of oleic acid. Through a factorial design 23 it was evaluated the effect of independent variables: temperature, molar ratio, oleic acid, alcohol and catalysts percentage, also evaluating, their interactions on the dependent variable percentage of conversion of oleic acid to methyl oleate. The compounds proved to be highly efficient in the studied reaction, with yields close esters 60.7%, 67.2%, 75.4%, 95.8%, 92.5%, 98.4%, 93.3 %, 92.5% and 89.5%, for OL, SIRAL 30, NM, NM SIRAL, OL / NM, OL / SIRAL NM5, OLS / SIRAL NM 5, OL / SIRAL NM10 and OLS / SIRAL NM10, respectively. The temperature and/or the molar ratio were the most influential variables studied in the reaction. The reuse tests performed indicated that the catalyst showed activity even after the 3º cycle. The catalysts were also evaluated for leaching test and the results showed that non-sulfated catalysts did not leach into the reaction medium, showing heterogeneity. The results showed that the catalysts studied have potential to be used in the oleic acid esterification reaction with methanol to produce biodiesel, although having the advantage of being easily removed from the reaction medium due to their magnetic properties. Besides that, they are not corrosive and do not require a washing step of the product, representing a less waste at the end of the process, making it more sustainable.